2008
DOI: 10.1016/j.atherosclerosis.2007.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Histological topographical comparisons of atherosclerosis progression in juveniles and young adults

Abstract: Background-The histologically topographic comparisons on atherosclerosis progression among three anatomical sites, mid-thoracic and lower abdominal aorta and left anterior descending coronary artery (LAD) were performed using a young population (age 15-34) from the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The procedures for immunohistochemical staining used in the present study were previously shown [7]. Two dual immunohistochemical stains were conducted for each sample: (1) macrophages (HAM-56) and alpha smooth muscle actin (1A4, Carpinteria); and (2) T-lymphocytes (anti-CD3, PS1) and B-lymphocytes (anti-CD20, L26) (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedures for immunohistochemical staining used in the present study were previously shown [7]. Two dual immunohistochemical stains were conducted for each sample: (1) macrophages (HAM-56) and alpha smooth muscle actin (1A4, Carpinteria); and (2) T-lymphocytes (anti-CD3, PS1) and B-lymphocytes (anti-CD20, L26) (Supplementary Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study using PDAY materials revealed the diversity of susceptibility to the progression of fatty streaks into preatheromas according to microscopic topographical differences in the thoracic aorta (TA) and the left coronary artery (LAD). In summary, based on differences in the histological features, the LAD was more vulnerable to lesion progression than the TA [7]. …”
Section: Introductionmentioning
confidence: 99%
“…As mentioned before, the animal models are predominantly setup to develop and study the very early fatty streak lesions with macrophage foam cells. Such lesions start very early in life in humans (even in infants and children) below the age of 15 [61][62][63][64][65][66][67][68]. Maternal hypercholesterolemia seems to strongly influence the development of atherosclerotic lesions in the young.…”
Section: Human Atherosclerosis and Animal Modelsmentioning
confidence: 99%
“…4 Importantly, the prevalence and severity of atherosclerosis in autopsied adolescents and young adults are associated with the presence of CVD risk factors. 5 Collegiate football players, linemen in particular, are a unique cohort of young adults who may be particularly vulnerable to future cardiac events.…”
mentioning
confidence: 99%